Successful Use of MTA Fillapex as a Sealant for Feline Root Canal Therapy of 50 Canines in 37 Cats. (June 2020) - Thorne, Susan; Johnston, Norman; Adams, Vicki J.
Intentional or unintentional pulp exposure of cat canines can lead to periapical disease, osteomyelitis, and oral pain. Root canal therapy (RCT) allows the retention of cat canines with pulp exposure by removing the infected pulp and replacing it with an inert material. This study used MTA Fillapex™ as a root canal sealant with gutta percha single cone obturation in 37 cats (50 canine teeth). Roots were classified as "successful, " "no evidence of failure (NEF), " or "failed" at 6-month radiographic reviews. Therapy was considered "successful" if a preoperative periapical lucency had healed or not formed after treatment and any preoperative external inflammatory root resorption (EIRR) had stabilized without progression. Therapy was categorized as "NEF" if a periapical lucency had remained the same or decreased in size but not completely resolved and any preoperative EIRR had stabilized without progression. "Failed" if a periapical lucency had occurred or increased in size posttreatment or if EIRR had developed or progressed posttreatment. Thirty-two canine teeth (64%) were classified as "successful, " 14 canine teeth (28%) were classified as "NEF, " and 4 canine teeth (8%) were classified as "failed". The study concluded that RCT using MTA Fillapex as a root canal sealant is a suitable endodontic treatment for fractured cat canines, especially those that are periodontally or endodontically challenged.